Conceptualisation, Systematic Review and Future Research Directions in the Broad Domains of Tourism Infrastructure - Gohwar Ahmad Wani; Arshid Hussain Peer; Ilma Rizvi; Shabir Hussain Malik (International Journal of Economics Development Research (IJEDR), 2023)
This paper explored the conceptualisation and research gaps in the field of tourism infrastructure. Key objective of the paper is to define tourism infrastructure and underline the areas explored by researchers and the fields uncharted yet. Systematic overview of existing research is given and briefly showed by details in papers. Articles published between 2007 and upto the end of 2021 has been selected to verify results. The details of author, objectives, methodology and results and conclusions are separated to help budding researchers to identify the research gaps. Nevertheless, the last section briefly describes the areas left untouched by studies for further research. The appraisal conducted shows that certain areas are not properly explored either conceptually, theoretically or empirically. Infrastructure gap is analyzed but the factors determining the functioning of infrastructure unbotched yet. Function of infrastructure to enhance service quality of environment is still unexplored and needs further empirical analysis. At the same time, there is a complete dearth of studies to analyse the contribution of sustainable infrastructure on dimensions of environment sustainability. Lastly, it is confirmed that the accessible literatures botched to give clear practical verification on the influence of tourism infrastructure on services and their influence on tourism resources management. As a result, it is anticipated that the study will add positively in said area and is obliging for lately researchers to conduct studies on uncharted dimensions.